2008
DOI: 10.2353/ajpath.2008.080339
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB Is a Critical Mediator of Ste20-Like Proline-/Alanine-Rich Kinase Regulation in Intestinal Inflammation

Abstract: Inflammatory bowel disease (IBD) is thought to result

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 77 publications
1
43
0
Order By: Relevance
“…Furthermore, mutation of the NF-κB element itself resulted in a 50% decrease of the TNF-α stimulated luciferase signal, indicating that the element is involved in the increased transcription of SPAK observed under inflammation. These studies confirmed increased expression of NF-κB and its translocation to the nucleus, alongside with increased SPAK mRNA and protein levels in mice treated with dextran sodium sulfate to induce colitis (320). …”
Section: Physiological Roles Of Spak and Osr1 In Mammalian Systemsmentioning
confidence: 54%
See 2 more Smart Citations
“…Furthermore, mutation of the NF-κB element itself resulted in a 50% decrease of the TNF-α stimulated luciferase signal, indicating that the element is involved in the increased transcription of SPAK observed under inflammation. These studies confirmed increased expression of NF-κB and its translocation to the nucleus, alongside with increased SPAK mRNA and protein levels in mice treated with dextran sodium sulfate to induce colitis (320). …”
Section: Physiological Roles Of Spak and Osr1 In Mammalian Systemsmentioning
confidence: 54%
“…As pro-inflammatory cytokines also lead to activation of p38, Merlin and coworkers examined SPAK mRNA expression in Caco2-BBE cells exposed to IFN-γ, TGF-β, and TNF-α treatment. They showed a 2.5-fold increased SPAK mRNA expression with interferon (323) and TNF-α (320). Note that the precise signaling pathway modulated by SPAK is likely cell-specific, as in hematopoietic cells, SPAK interacts with the TNF receptor RELT (Receptor Expressed in Lymphoid Tissues), leading to activation of both p38 and JNK signaling (228).…”
Section: Physiological Roles Of Spak and Osr1 In Mammalian Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on recent studies, the pathogenesis of IBD seems to involve a complex interplay between certain genetic, environmental, and immunological factors. In particular, an unbalanced activation of the mucosal immune system driven by the commensal flora in a genetically susceptible host appears to cause intestinal inflammation in IBD patients [1][2][3][4][5][6]. The activation of the mucosal immune system is characterized by production of proinflammatory cytokines [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…lactis BI07-HT29 cell early interaction. TNF-␣ was selected because this cytokine has been reported to play a central role in intestinal inflammation (18,40).…”
mentioning
confidence: 99%